Taking the Jews out of the Equation Galatians 6.12-17 as a Summons to Cease Evading Persecution - Prokhorov, Alexander V. (2013)
This reading of Gal. 6.12-17 presents an alternative to theories that consider the ‘problem of the Galatians’ to be the result of the activity of Judaizers. Rhetorical clues in 6.12-17 point to an intra-Gentile issue and lead to the conclusion that Paul’s discourse is not concerned with matters of Jewish religion and culture. Paul’s rhetoric deals with a distinctly socio-logistical issue that had confronted the Galatian neophytes. The ‘Galatian problem’ is construed as a tendency to evade intimidation and maltreatment which often befell Gentile Christians who reduced or discontinued their participation in Roman imperial rituals. Paul makes it plain to his audience that the reception of outward signs indicating afﬁliation with the synagogue, despite all the immediate beneﬁts of such an action, is tantamount to a betrayal of the gospel whose essence is linked to suffering.
Keywords: Suffering; Persecution; Pauline rhetoric; Jews; the ‘problem’ of Galatians; Circumcision